Time-motion study of female field hockey - Boddington, M.; Lambert, M.; St. Clair Gibson, A.; Noakes, T. (2001)
The physical demands of the 'modern' hockey match were determined using a video analysis to quantify the displacement of the female players (n = 11) every 15 seconds during a league match (n = 3). These data for each match were analysed using ANOVA with repeated measures and a covariance for playing time. The mean total displacement was 3914 ± 770 m in 63.3 ± 9.5 minutes or approximately 61 m per minute of playing time. The total displacement in match 1(4250 ± 752 m) was greater than match 2 (3850 ± 642 m; P = 0.0002) and match 3 (3864 ± 632 m; P = 0.001). Displacement per minute playing time was greater in match 1(65 ± 8.4 m.min-1) than in match 2 (58 ± 3.7 m.min-1 P = 0.005) and match 3 (59 ± 4.6 m.min-1 P = 0.046). There were significant decreases in displacement in the second half compared to the first (P = 0.01 total displacement and P = 0.009 displacement per minute playing time). There were no significant differences between the mean displacement and the mean speed (P = 0.33 and P = 0.31 respectively) for the 3 matches or the 2 playing halves (P = 0.19 and P = 0.20 respectively). Mean heart rate was significantly higher during match 1 (176 ± 5 beats.min-1) than matches 2 and 3 (162 ± 5 beats.min-1 and 166 ± 4 beats.min-1, matches 2 and 3 respectively). The mean heart rate during the first half (171 ± 7 beats.min-1) was higher than the second (165 ± 9 beats.min-1) (P = 0.03). An analysis of the subjective data found that the players perceived match 1 to be harder than match 2 or 3 (P < 0.05) and match 3 to be harder than match 2 (P < 0.05). The preparation and the subjective feelings prior to the 3 matches were perceived to be the same (P = 0.67 and 0.09 respectively). In conclusion, the average displacement during a match was approximately 4 kilometres and the average displacement covered during each 15-second period was about 15 m, which included frequent changes in direction and speed.